The contested terrain of land governance reform in Myanmar - Suhardiman, Diana; Kenney-Lazar, M.; Meinzen-Dick, Ruth S. (Informa UK Limited, 2019)
State control of land plays a critical role in producing land dispossession throughout the Global South. In Myanmar, the state’s approach towards territorial expansion has driven the country’s system of land governance, resulting in widespread and systemic land grabbing. This article investigates ongoing land governance reforms as key terrains for contesting such abuses of power. Employing a relational land governance approach, we view reform processes as shaped by changing power-laden social relations among government, civil society, and international donor actors. Legal and regulatory reforms in Myanmar potentially act as sites of meaningful social change but in practice tend to maintain significant limitations in altering governance dynamics. Civil society organizations and their alliances in Myanmar have played an important role in opening up policy processes to a broader group of political actors. Yet, policies and legal frameworks still are often captured by elite actors, becoming trapped in path dependent power relations.